Peningkatan Minat Belajar Siswa Melalui Game Based Learning Berbasis Tebak Kata pada Materi Bahaya Merokok, Minuman Keras dan Narkoba - Afgenesya, Denata Novenda; Wiguno, Lokananta Teguh Hari; Marzuqi, Anang (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The present study posits that the utilization of the play approach is efficacious in enhancing students' motivation to learn in school activities. The findings of the research indicate that play activities encourage students to be more active and creative. The implementation of this research, which took place in two cycles, involved a specific classroom action. The results of this implementation provided evidence that the play approach can serve as an appropriate alternative to increase students' active participation in learning activities. A substantial increase in learning motivation was observed following the implementation of the strategy. This finding is supported by data collected through observation, documentation, and questionnaires. The study's findings indicate that the play approach has the potential to significantly enhance the interest and learning motivation of students in class V A ICP SD Laboratorium UM in learning activities. Consequently, the implementation of this approach in learning activities is strongly advocated to foster a more conducive and effective learning environment.